THE PROTECTION OF INTELLECTUAL PROPERTY RIGHTS IN CYBERSPACE (JOURNAL OF ANALYTICAL SYNERGY AND SCIENTIFIC HORIZON, 2025)
This article examines the importance of online IP protection, focusing on Uzbekistan’s legal framework, international agreements, and foreign practices. Through comparative analysis, it highlights gaps in legislation and proposes practical improvements. The study offers insights into legal complexities and emphasizes the need for stronger digital rights protection, contributing to global discussions on intellectual property in the digital age.